THE EFFECT OF TELECOMMUTING ON WORK-LIFE BALANCE, JOB SATISFACTION AND TURNOVER INTENTION - Rokhman, Afif Nur; Raharjo, Kusdi; Norman, Teuku (Erudio Journal of Educational Innovation, 2025)
In a company, employees also conclude as an investment that plays a massive role in productivity. If the employee doesn't feel valued by the company, it will lead to resignation, which can increase the turnover index. Several aspects, such as job stressors, work-life balance, and work-from-home or anywhere options, become one-factor affecting employee satisfaction with the company. This study examines how telecommuting and work-life balance affect job satisfaction and turnover intention. Using SMART PLS 3, this study examines 114 employees' behavior on PT. FEM regarding those variables stated. The result shows that all the hypotheses are accepted significantly negatively and positively.